Pengaruh Book Tax Differences Terhadap Kualitas Laba Pada Perusahaan Sektor Barang Konsumsi Di Indonesia - Rianto -; Dwi Novi Murtiani (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2019)
This research aimed to determine the effect of book tax differences to the quality of earnings on the next period in manufacturing companies in the customer goods industry sectors listed on the Indonesia Stock Exchange (BEI) from 2010 to 2013. The types of data used in this research was quantitative data methods with descriptive analysis testing, and statistical analysis was linear regression. The sampling methods used was purposive sampling. The result of this research indicate that large positive book tax differences is not significant effect on the quality of earnings. Companies with large positive book tax differences not shown to have lower persistence than firms with small book tax differences. Large negative book tax differences is significant effect on the quality or earnings. Companies with large negative book tax differences shown to have lower persistence than firms with small book tax difference